Evaluation of the efficiency of some pheromone traps in attracting adults of the peach fruit fly Bactrocera zonota (Saunder) (Diptera: Tephretidae) in an orchard in Karbala Province, Iraq - Gaduaa, Alaa Abbas; Kareem , Ali Abdulhusien (Journal of Kerbala for Agricultural Sciences, 2023)
A study was conducted to evaluate the efficiency of the integrated control program for the peach fruit fly. Different attractant pheromone traps and treatments of fungi, biocides and some agricultural operations to attract and catch adult insects in citrus orchards in Karbala during the fall season 2021-2022. The fungi Beuveria bassiana, Metarhizum anisopliae and the pesticide Balizin S165% were used with different pheromone traps Delta trap (Jackson red trap), Tefrey yellow trap, Spanish Olipe trap, and the local trap. Also, within the integrated control program, a study was conducted on the efficiency of attractant pheromone traps with the pesticides Tondexir EC80%, Success 0.02CB, and some agricultural operations such as wrapping the fruits in paper bags, tilling the soil, cleaning the weeds, and covering the soil with polyethene. The treatment of M. anisoplia with the two traps of Jackson (fruit fly pheromone) and Tefrey trap (a new peach fly pheromone) gave 95.8 % of effect through attraction within 6 days. As for the two treatments of the B. bassiana fungus and the pesticide Balizin with the two traps of Jackson and the Trap of Tefrey, the pheromone traps were almost identical in the same effect in attraction and entrapment reached 74.5 and 73.09, respectively. There were significant differences in the number of adults attracted to the traps in the study site, where the efficiency of pheromone traps was characterized by the agricultural operations of covering the soil with polyethene, soil ploughing and cleaning weeds with two Jackson traps (fruit fly pheromone) and the local trap gave the highest rate of effect by trapping the most significant number of adults over 6 days. In a study of the efficiency of all the treatments used in the integrated insect control program in reducing the infection rate on citrus trees, it was noted that all the treatments used caused a decrease in the average number of infected fruits during the first, second, and third weeks. The statistical analysis proved that the rate of infected fruits of citrus trees in the different treatments did not differ statistically among them. Based on the study’s results, attractive pheromone traps can target adult insects as one of the components of integrated control programs for the peach fruit fly.